Izmenenie skorostno-silovykh pokazatelei nervno-myshechnogo apparata pod vliyaniem priemov massazha - Povarishenkova, Ju. A. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
The main purpose of this study was to research the influence of different massage practices to nerves and musclar apparatus. 43 sprinters 17-22 years of age were inspected at rest and after five-minutes of different massage practices. Only traditional kinds of sports massage were using during the experiment, such as striking, shaking, wringing, petrissage, embrocation and percussion. Analysis of inquired data permited to evaluate an influence of the massage practices to the examined phenomenon and to complete a picture of muscular speed and power marks modifications forming. It was also shown by the researcher, that the different massage practices induse unequal directive, quantitative and dynamic changing of solitary contraction parameters.